Zainichi Cinema Korean-in-Japan Film Culture - Dew, Oliver; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book examines how filmmakers, curators, and critics created a category of transnational, Korean-in-Japan (Zainichi) Cinema, focussing on the period from the 1960s onwards. An enormously diverse swathe of films have been claimed for this cinema of the Korean diaspora, ranging across major studio yakuza films and melodramas, news reels created by ethnic associations, first-person video essays, and unlikely hits that crossed over from the indie distribution circuit to have a wide impact across the media landscape. Today, Zainichi-themed works have never had a higher profile, with new works by Matsue Tetsuaki, Sai Yoichi, and Yang Yonghi frequently shown at international festivals. Zainichi Cinema argues that central to this transnational cinema is the tension between films with an authorized claim to "represent", and ambiguous and borderline works that require an active spectator to claim them as images of the Korean diaspora.
Introduction: Koreans-in-Japan, on-screen -- 1. 1968/2004: Bridging Imjin River -- 2. Screening the Zainichi subject -- 3. Excavating the Zainichi yakuza film -- 4. 'Pacchigi Power!': the 'coming out' melodrama -- 5. Arirang kamikaze: screening the memory wars -- 6. Intimate ethnographies: three family portraits -- Conclusion.
Keywords: Motion pictures-Asia.; Asian Cinema and TV